Assessment of Adherence to COVID-19 Diagnosis and Treatment Guidelines in Outpatient Settings: Perspectives of Medical Interns at Tabriz University of Medical Sciences - Maryam Baradaran Binazir; Fariba Heidari; Sasan Saeedifar (Taṣvīr-i salāmat)
Background. The Ministry of Health had developed guidelines for the management of COVID-19 patients in outpatient settings. Despite the development of a national guideline and its importance, no study had been conducted on compliance with the guidelines for the diagnosis and treatment of COVID-19. Therefore, the aim of this study was to evaluate the extent to which these guidelines were followed in outpatient services, specifically from the perspective of interns at Tabriz University of Medical Sciences. Methods. This study was cross-sectional, involving all 100 interns who were completing their clinical rotations in COVID-19-related departments during February and March 2022. The data collection tool was a checklist, which was developed using the guideline for the diagnosis and treatment of COVID-19 published by the National Scientific Committee for COVID-19 Management in January 2022. The checklist comprised 29 items and was validated for both validity and reliability by relevant specialists. Results. This study included 100 medical interns from Tabriz University of Medical Sciences. Fifty interns completed their rotations in the emergency department, and the remaining 50 in outpatient clinics. The mean compliance scores with COVID-19 guidelines, as reported by emergency department and outpatient clinic interns, were 26.54 ± 3.34 and 26.73 ± 2.16, respectively (P = 0.124). The lowest compliance rate (37%) was observed for item 22 ("Azithromycin and other antibiotics should not be used without strong suspicion of concomitant bacterial infection"). However, the majority of checklist items (89.65%) demonstrated excellent compliance. Conclusion. Overall, interns reported good adherence to COVID-19 guidelines in both the outpatient clinic and emergency department settings. However, instances of inappropriate antibiotic and vitamin supplement prescription were observed. To mitigate unnecessary treatments, further efforts to improve staff awareness and adherence are needed.